Regenerative effects of spring water-derived bacterial lysates on human skin fibroblast in in vitro culture: preliminary results. Issue 11 (November 2019) - Nicoletti, Giovanni; Saler, Marco; Tresoldi, Marco Mario; Faga, Angela; Benedet, Mattia; Cristofolini, Mario
Objective: Previous studies have shown regenerative power of the skin with Comano (Trento, Italy) spring water and resident non-pathogenic microflora. This study investigated the action of bacterial lysates that were isolated from Comano spring water on in vitro culture of human skin fibroblasts. Methods: For this study, we selected the following four bacterial lysates: L1 (closest relative: Rudaea cellulosilytica ), L2 (closest relative: Mesorhizobium erdmanii ), L3 (closest relative: Herbiconiux ginsengi ), and L4 (closest relative: Fictibacillus phosphorivorans ). Human fibroblasts were cultured under Dulbecco's modified Eagle's medium (DMEM) with bacterial lysates added or DMEM (controls). Cell proliferation was evaluated by spectrophotometric absorbance analysis after the XTT-Microculture Tetrazolium Assay. Results: At 24 hours, cultures with L2, L3, and L4 showed a higher absorbance compared with controls. At 48 hours, cultures with L1, L2, and L3 showed slightly lower absorbance compared with controls, and culture with L4 showed a higher absorbance than in the other experimental conditions. At 72 hours, absorbance was lower in cultures with L1, L2, and L3 than in controls, and absorbance was higher in culture with L4 than in the other experimental conditions. Conclusions: Our study indicates a favorable action of Comano spring water microbiota on proliferation of human skin fibroblasts.